Susceptibility of perioperatively isolated bacteria to cefazolin - a pilot study - Pevec, Teodor (Zdravniški vestnik, 2014)
Introduction: The selection of perioperative prophylactic antibiotic is based on the expected bacterial flora in the site of the surgical procedure and its susceptibility to antibiotics. Recent reports on coagulase-negative staphylococci, typical representatives of skin flora, showed their resistance to methicillin. We may wonder whether cefazolin is still the antibiotic of choice for surgical prophylaxis in clean surgical procedures. Patients and methods: In a prospective study we included patients who underwent surgical treatment for various types of injuries. Three swab samples were taken in each patient. The first sample was taken from the incision site before the operating field was prepared. The second swab was taken after the operating field preparation and the third was taken at the end of the operation. The results of microbial growth and the susceptibility to antibiotics were recorded. The incidence of a wound infection in patients included in the study was followed prospectively. In the case of infection, the bacteria isolated intraoperatively during the surgical revision were compared to the bacteria isolated perioperatively at the time of the first surgery. All patients received cefazolin in a single dose of 1 to 2 grams according to their weight pre-operatively. The antibiotic was administered 20 minutes before the incision. No additional antibiotic dose was given after surgery. Results: Before the operating field was prepared, swabs were sterile in two patients (6.4%), at the end of preparation the swabs remained sterile in 22 (71%) patients and at the end of surgery in 13 (42%) out of the 31 injured patients. There were no methicillin-resistant swab cultures after operative field preparation, but at the end of surgery in four patients (13%) the swab cultures grew methicillin resistant Staphylococcus epidemidis. Bacillus sp. was isolated in five patients (16.1%) after operative field preparation and in two patients (6.4%) at the end of surgery. The susceptibility of the Bacillus sp. was not determined because of the lack of standardized testing method. Conclusion: In a pilot study we found a large proportion (4/31) of patients in whom colonization of the operative field with cefazolin-resistant bacteria developed during the surgical procedure. The result of our pilot study challenges the guidelines recommending cefazolin for surgical prophylaxis in clean surgery. Further studies in larger patient population are needed.
Keywords: infection; kužnina; občutljivost bakterij; okužbe; susceptibility of bacteria; swab